2017
DOI: 10.1021/acs.jpcc.6b09793
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of PTCDA on Ge(001)

Abstract: Adsorption of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) on the Ge(001) surface was studied using scanning tunneling microscopy (STM), scanning tunneling spectroscopy (STS), and the density-functional theory (DFT) calculations. Only single adsorption configuration of the PTCDA molecule was observed at low coverages on the Ge(001) at room temperature, unlike on the Si(001) where several adsorption configurations were reported. This indicates that the PTCDA molecules on the Ge(001) were more mobile t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
5
10
0
Order By: Relevance
“…Moreover, it should be kept in mind that STM measures the local density of states, not the positions of the atoms, and that the appearance of an adsorbate in STM can be deceiving. [124][125][126][127][128][129][130][131] Also, the composition of the substrate surface and its impact on the interface structure is often not a priori clear. Many metal-organic interfaces incorporate adatoms from the substrate, 8,82,132,133,[133][134][135][136][137][138][139] which have a decisive impact on the geometry of the organic layers as well as the interface properties.…”
Section: Structure Of the Interfacementioning
confidence: 99%
“…Moreover, it should be kept in mind that STM measures the local density of states, not the positions of the atoms, and that the appearance of an adsorbate in STM can be deceiving. [124][125][126][127][128][129][130][131] Also, the composition of the substrate surface and its impact on the interface structure is often not a priori clear. Many metal-organic interfaces incorporate adatoms from the substrate, 8,82,132,133,[133][134][135][136][137][138][139] which have a decisive impact on the geometry of the organic layers as well as the interface properties.…”
Section: Structure Of the Interfacementioning
confidence: 99%
“…3 . Prior studies have moreover shown that PTCDA molecules, prior to their dehydrogenation, are mobile on Ge(001) at temperatures >180 °C and that non-covalent interactions among PTCDA molecules are favorable under particular arrangements leading to clustering 56 , 57 . While their mobility following dehydrogenation has not yet been studied, the PAH molecules studied, here, likely remain hydrogenated throughout the initiation stage and at the beginning of the nanoribbon growth stage (as the temperature is increased from room temperature to 920 °C) thereby providing the opportunity for PAH diffusion and/or clustering and further establishing the plausibility of the scenario presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PTCDA growth has been investigated on pristine silicon and germanium surfaces, like Si(111), Si(001), Ge(111), and Ge(001), as well as on III–V semiconductor compound surfaces, like GaAs(001) and InSb(001), among others. In the present paper, two prototypical examples that have been studied by STM are reviewed.…”
Section: Ptcda On Clean Semiconductorsmentioning
confidence: 99%